Renal insufficiency associated with excessive lead exposure. Issue 6059 (19th February 1977) - Campbell, B C; Beattie, A D; Moore, M R; Goldberg, A; Reid, A G
Abstract : Water lead concentrations were measured in 970 households throughout Scotland. Blood lead concentrations were measured in 283 people living in houses with water lead levels of over 0-48 mumol/l (100 mug/l). A highly significant correlation was found between lead concentrations in water and blood. Raised blood lead concentrations were associated with renal insufficiency, reflected in raised serum urea concentrations, and with hyperuricaemia, although there was no evidence of clinical disease in any of the affected people. This is further evidence that excessive lead in domestic water supplies has a harmful effect on the community's health.